Luminescence and structural properties of Ca1-xZrO3:Eux: An experimental and theoretical approach - Assis, Marcelo; Oliveira, Marisa Carvalho de; Gouveia, Amanda Fernandes; Ribeiro, Lara Kelly; Rosa, Ieda Lucia Viana; Ribeiro, Renan Augusto Pontes; Andrés, Juan; Longo, Elson (Eclética Química, 2022)
The influence of Eu3+ cations in the host matrix of CaZrO3 was investigated by analyzing its luminescence and structural properties. The Ca1-xZrO3:Eux crystals (x = 0.01, 0.02, 0.04, and 0.08 mol%) were obtained by a simple sol-gel method followed by a soft thermal treatment without any surfactant. The structural characterization was performed at short-, medium- and long-distance to verify the effect of the dopant in the host matrix. To endorse the experimental results, first-principles calculations were performed by using the CRYSTAL program associated with the density functional theory. The luminescence profile of the sample was investigated by analyzing the excitation and emission spectrum monitoring the emission at 614 nm and excited at 394 nm, noting that the sample Eu-doped with 0.08 mol% has greater emission intensity. The color variations of the characteristic emissions of Ca1-xZrO3:Eux crystals were evaluated according to the Commission Internationale de L’Éclairage, observing a red shift for all Eu-doped samples. A general luminescence scheme was proposed combining the density of state and the band structure calculations.